2021
DOI: 10.3390/ijms222312921
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-1 Inhibition Reactivates Wnt/β-Catenin Signaling in Rhabdomyosarcoma, Induces Myogenic Markers In Vitro and Impairs Tumor Cell Survival In Vivo

Abstract: The Wnt/β-catenin signaling pathway plays a pivotal role during embryogenesis and its deregulation is a key mechanism in the origin and progression of several tumors. Wnt antagonists have been described as key modulators of Wnt/β-catenin signaling in cancer, with Dickkopf-1 (DKK-1) being the most studied member of the DKK family. Although the therapeutic potential of DKK-1 inhibition has been evaluated in several diseases and malignancies, little is known in pediatric tumors. Only a few works have studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Therefore, at first glance, the WNT5A-induced inhibition of the WNT/β-Catenin pathway seemed to be associated with a decrease in cell proliferation and migration in both colon cancer and RMS cells. However, this is rather not the case, since a recent study showed decreased proliferation with concomitant activation of WNT/β-Catenin signaling in RMS cell lines deficient for DKK1 ( 15 ) and since we recently showed that canonical WNT signaling and β-Catenin do not affect aggressiveness of RMS cell lines or in a murine RMS model ( 17 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, at first glance, the WNT5A-induced inhibition of the WNT/β-Catenin pathway seemed to be associated with a decrease in cell proliferation and migration in both colon cancer and RMS cells. However, this is rather not the case, since a recent study showed decreased proliferation with concomitant activation of WNT/β-Catenin signaling in RMS cell lines deficient for DKK1 ( 15 ) and since we recently showed that canonical WNT signaling and β-Catenin do not affect aggressiveness of RMS cell lines or in a murine RMS model ( 17 ).…”
Section: Discussionmentioning
confidence: 95%
“…However, it has been reported that stimulation of RMS cell lines with recombinant WNT3A leads to nuclear translocation of β-Catenin and blocks cellular proliferation ( 13 , 14 ). In addition, downregulation of the main inhibitor of WNT/β-Catenin signaling Dickkopf1 leads to expression of active β-Catenin and inhibition of proliferation and invasion of RMS tumor cells ( 15 ). These results imply that activation of WNT/β-Catenin signaling has antitumoral effects in RMS.…”
Section: Introductionmentioning
confidence: 99%
“… 34 Beyond the CTNNB1 mutation, the Dickkopf (DKK) family is known for fine‐tuning Wnt activity. 35 For example, DKK1 is defined as an agonist of the Wnt/β‐catenin signalling pathway in HCC 36 but an antagonist in rhabdomyosarcoma 37 and ovarian cancer. 38 Similarly, DKK4 affects tumourigenesis and development by modulating the Wnt/β‐catenin signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…When DKK was inhibited, β-catenin was reactivated and focal adhesion kinase (FAK) was consequently modulated, which had a favorable impact on in vitro expression of myogenic markers and decreased the proliferation and invasion of cells. Thus, adoption of treatment modalities based on the reactivation of Wnt/β-catenin signaling, intertwined regulatory pathways shall be taken into consideration in RMS patients [ 67 ].…”
Section: Wnt Signaling In Rhabdomyosarcomamentioning
confidence: 99%